2013
DOI: 10.1182/blood-2012-08-453738
|View full text |Cite
|
Sign up to set email alerts
|

LAMP1/CD107a is required for efficient perforin delivery to lytic granules and NK-cell cytotoxicity

Abstract: Key Points• LAMP1 silencing inhibits cytotoxicity of human NK cells.• LAMP1 is important for perforin trafficking to the lytic granules and granule movement.Secretory lysosomes of natural killer (NK) cells, containing perforin and granzymes, are indispensable for NK-cell cytotoxicity because their release results in the induction of target-cell apoptosis. Lysosome-associated membrane protein (LAMP) 1/CD107a is used as a marker for NK-cell degranulation, but its role in NK-cell biology is unknown. We show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(111 citation statements)
references
References 50 publications
1
109
0
1
Order By: Relevance
“…During NK cell-mediated cytotoxicity, a transient Ca 2+ influx is induced in the target cells, which is necessary for the apoptosis triggered by the endocytosed GrB (21,37,38). It is known that Cx43 regulates Ca 2+ influx in various cell types (39), and we have previously reported that Cx43 regulates Ca 2+ signaling at the IS in T cells (14).…”
Section: Cx43-mediated Intercellular Communication Contributes To An mentioning
confidence: 95%
See 1 more Smart Citation
“…During NK cell-mediated cytotoxicity, a transient Ca 2+ influx is induced in the target cells, which is necessary for the apoptosis triggered by the endocytosed GrB (21,37,38). It is known that Cx43 regulates Ca 2+ influx in various cell types (39), and we have previously reported that Cx43 regulates Ca 2+ signaling at the IS in T cells (14).…”
Section: Cx43-mediated Intercellular Communication Contributes To An mentioning
confidence: 95%
“…5B). CD107a (LAMP-1)-deficient cells have reduced levels of perforin in lytic granules and disturbed motility of the lytic granules, which leads to the inability to deliver apoptosis-inducing GrB to target cells and to the inhibition of NK cell cytotoxicity (36,37). We evaluated CD107a expression on the surface of NK cells; however, no difference in CD107a levels were observed upon blockade of Cx43-GJs in NK cells and K562 cells (Fig.…”
Section: Cx43-mediated Intercellular Communication Contributes To An mentioning
confidence: 99%
“…For example, the lysosomal Ca 2+ -sensor ALG-2 (also known as PDCD6) promotes interaction of the lysosomal Ca 2+ channel transient receptor potential mucolipin 1 (TRPMNL1 or MCOLN1) with dynein-dynactin to regulate centripetal transport of lysosomes in response to changes in Ca 2+ levels (Li et al, 2016b). There are also lysosomal transmembrane proteins that regulate retrograde transport, such as LAMP-1 and LAMP-2, which promote coupling of lysosomes to dyneindynactin (Huynh et al, 2007;Krzewski et al, 2013), and transmembrane protein 106B (TMEM106B), which inhibits retrograde transport of lysosomes in neuronal dendrites through interaction with the microtubule-associated protein 6 (MAP6) (Schwenk et al, 2014). Finally, the snapin subunit of the BORC and BLOC-1 complexes (Pu et al, 2015) has also been reported to couple lysosomes to dynein, particularly in hippocampal neurons (Cai et al, 2010).…”
Section: Retrograde Transportmentioning
confidence: 99%
“…LAMP1/CD107a appears on the cell surface following the fusion of lysosomes with the plasma membrane, and therefore is therefore used as a functional marker of degranulation of CD8 + CTLs [24] and NK cells [25]. Moreover, LAMP1/CD107a is required for efficient perforin delivery to lytic granules and subsequent cytotoxicity [17]. We observed that infiltrated CD4 + T cells consistently expressed constantly higher levels of LAMP1/CD107a and additional inflammatory cytokines, particularly type I interferon [10,26,27].…”
Section: Direct Migration Of Ccirculating Cd4 + T Cells Directly Migrmentioning
confidence: 73%